Tingkat Efektivitas Program Magang di Prodi Manajemen Universitas Buana Perjuangan Karawang - Mochamad Alfi Apriansyah; Uus Mohammad Darul Fadli; Laras Ratu Khalida (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to evaluate the effectiveness of the internship program in improving the skills and competencies of students at the Faculty of Economics and Business, Universitas Buana Perjuangan (UBP) Karawang. The research is motivated by the importance of preparing graduates to face the challenges of the workforce, as well as findings that some students feel the benefits of the internship program have not been fully optimized. A qualitative approach with a case study method was employed to explore students’ experiences and perceptions. Data were collected through in-depth interviews with ten students who had completed the internship program, supported by literature studies. The results indicate that the internship program is considered “fairly effective” by students, with several aspects still requiring improvement. Internship placement, technical guidance, and structured evaluation are identified as areas in need of enhancement. These findings highlight the necessity for better coordination between the university and partner institutions to achieve more optimal outcomes.